151k views
0 votes
Theo started to solve the quadratic equation (x + 2)2 - 9 = -5. He added 9 to both sides and the resulting equation was

(x + 2)2 = 4. Next, he took the square root of each side.
Which was the resulting equation of that step?

2 Answers

3 votes

Answer:

A

Explanation:

ed 2020

User AngryUbuntuNerd
by
5.5k points
4 votes

Answer:


x + 2 = \pm √(4)

Explanation:

(x + 2)^2 - 9 = -5

Add 9 to both sides.

(x + 2)^2 = 4

Take the square root of both sides.


x + 2 = \pm √(4)

User Mohamed Khalil
by
5.9k points